(untitled) (Journal of Engineering, 2023)
This manuscript studied the effect of U-CFRP wrapped sheet anchorage on the flexural performance of unbonded post-tensioned PC members subjected to partial strand damage and strengthened using CFRP Near-Surface Mounting techniques. The program includes six girders as a control girder, a girder with strand damage of 14.2%, and four girders strengthened by CFRP laminates using the NSM technique with and without U-CFRP wrapped sheet anchorages. The testing results show that the strand damage of 14.2% has reduced the flexural strength of the girder by 5.71%. The NSM-CFRP laminate has a significant effect on flexural strength by 17.4%. On the other hand, the application of end U-CFRP wrapped sheet anchorages improves flexural strength by 27.97% and enhances ductility. The intermediate and successive U-CFRP sheet anchorages increase the flexural strength by 36.56% and 32.61%, enhancing the stiffness at all loading stages and improving the ductility. Semiempirical equations were developed to determine the actual stress of unbonded strands considering the effect of U-FRP-wrapped anchorages.